INVESTIGATION OF THE RELATIONSHIP BETWEEN BOND GRINDABILITY TEST AND STATIC AND DYNAMIC STRENGTH OF ROCKS - Yakup Umucu; Yaşar Hakan Gürsoy (Eskişehir Osmangazi Üniversitesi Mühendislik ve Mimarlık Fakültesi Dergisi, 2022)
The Bond method is widely used in the design of grinding circuits in an ore preparation plant, sizing of mills, determining power requirements and determining and measuring performance, and for materials considered to be comminution. Its use as a standard is very common in the industry as it provides satisfactory results in all industrial applications. The dynamic method was developed as an alternative to static methods in determining the mechanical properties of materials. There are studies investigating the static and dynamic properties of materials and revealing the relationship between these parameters. Previously, a lot of work were done between mechanical tests and grinding. However, in these studies, the relationships were only revealed with equations. Research which is mechanical property closest to the grinding mechanism was not made. In this study, the relationship between grinding and static and dynamic compressive strength was investigated. Dynamic compressive strength was also determined by the Hopkinson dynamic test. For the first time, the relationship between grinding and compressive strength based on the Hopkinson dynamic test was demonstrated. A relationship with a value of R2:0.82 and 0.738 was obtained between grindability and compressive strength depending on the Hopkinson dynamic test.